Demographics and disposition as predictors of the application of critical thinking skills in nursing practice - Rodriguez, Grace, author; Davies, Timothy Gray, advisor; Morgan, George A., committee member; Vigil, Patricia Mestas, committee member; Coronado, Herlinda M., committee member (Colorado State University. Libraries, 2000)
Nurses in various care units are involved in making life and death decisions and must utilize critical thinking abilities while applying critical thinking skills for assessing human responses to actual or potential problems. Expertise in nursing practice exists when the nurse has developed the ability to use appropriate nursing knowledge and the application of critical thinking skills while delivering patient care. The purpose of this study was to explore the variables of age, degree, career path, gender, years of clinical experience and personality as predictors for the application of critical thinking skills in nursing practice. The sample (N=60) was registered licensed nurses employed at a public hospital. A quantitative design was utilized with an associational approach. The California Critical Thinking Disposition Inventory (CCTDI), a demographic questionnaire, and the Observation of Critical Thinking Skills Application Tool, were selected to measure the variables. Data were analyzed using descriptive and inferential statistics. A significance level of 0.05 was selected. None of the individual predictor variables were statistically significant. Two multiple regressions were computed to see if there was significant combination of predictor variables with the application of critical thinking skills of the nurse in nursing practice. Pearson product moment correlation coefficients were computed to test the association or relationship between the critical thinking skills application and the CCTDI, age and experience. The t-test, with 2-tail tests for significance was also computed to compare gender, career paths, and degree on the critical thinking application in nursing practice on the California Critical Thinking Disposition Inventory. Several statistically significant supplemental findings were identified by reexamining questions similar to the research questions, but with the critical thinking dispositions as the dependent variables. Implications for further research include replication of this study in multiple clinical settings and in various hospitals. Research examining the need for real world experiences during education preparation to show relationship of clinical competence to critical thinking skills needs to be validated. In conclusion, these data should enhance understanding of the relationships between demographics and personality emphasizing that skills and dispositions are mutually reinforced and should be taught and modeled simultaneously to develop an approach for developing nurses to enter nursing practice.
Keywords: community colleges; health education; nursing; demographics; critical thinking